Rural population of Kazakhstan: demographics, statistics and trends (Journal of Economic Research & Business Administration, 2021)
The article considers the problems of aggravation of the demographic situation in rural areas, causedon the one hand by the mechanical outflow of the able-bodied population and, on the other hand, bynatural decline in fertility and relatively short life expectancy. Meanwhile, Kazakhstan has adopted astate program for the development of the agro-industrial complex for 2017 – 2021 years. Agriculture,as the core of the agro-industrial complex, has important tasks to ensure the physical and economicaccessibility of food to the general population, increase the efficiency of the use of natural resources,develop agricultural science and transfer of technologies, introduce digital technologies and improve thequality of life of the rural population. Declining demographic potential in rural areas in the future mayadversely affect the rate of reproduction of the population as a whole, the state and even the degradationof rural areas. The purpose of the article is not only a statistical analysis of the rate of reproduction of therural population, a study of the demographic situation in rural areas, but also the justification of a set ofmeasures to prevent demographic threats, solve the problem of food security, and sustainable social andeconomic development of rural areas. To achieve the goal, dialectical, historical, statistical-economic,comparative methods were used. Authors allocate the labor capacity of rural territories as a major factorof ensuring competitiveness of the rural area, the region and the country in general.Key words: rural population, demography, migration, outflow, labor resources.